The Relationship between Parental Feeding Style with Toddler Diet in the Locus Stunting Area in West Java - Jatnika, Ratna; Pebriani, Lucia Voni; Fatimah, Siti Nur; Haffas, Mustofa (International Journal of Psychosocial Rehabilitation, 2020)
This research is a correlational study to find out the relationship between Parental Feeding Style with Toddler Diet in the Locus Stunting Area in West Java. Parental Feeding Style consists of Encouragement Feeding Style, Instrumental Feeding Style, Emotional Feeding Style, and Control Feeding Style. The Diet of Toddlers is measured using “Isi Piringku” nutritional program, which consists of Proper Feeding and Nutritional Composition. Data was collected in 4 districts which are locus stunting areas in West Java, which consisted of 173 health workers. The data obtained were processed using the Pearson product-moment correlation. The results of data processing showed a relationship between Control Feeding Style with Nutritional Composition (r = 0.183; p = 0.023) and Encouragement Feeding Style with Nutritional Composition (r = 0.166; p = 0.036). This result shows that according to the perception of health workers in the locus stunting area, parents who provide food with the right nutritional composition are parents who apply the Control Feeding Style and Encouragement Feeding Style.